2020
DOI: 10.1016/j.healun.2020.04.021
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in a pediatric heart transplant recipient: Emergence of donor-specific antibodies

Abstract: turbo-field-echo sequence-4 chamber view). No focal fibrosis was detected in late gadolinium enhancement sequences (Figure 1c, single-shot inversion recovery sequence-4 chamber view). Global edema in T2 weighted images was visible (Figure 1d, T2 [short tau inversion recovery] sequence-3 chamber view) as well as globally elevated T2 (56 ms, referent 48 § 3 ms) (Figure 1e, T2 mapping-short-axis view) and T1 (1,090 ms, referent 989 § 28 ms) (Figure 1f, T1 mapping -short-axis view) mapping times, suggesting acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 5 publications
0
41
0
1
Order By: Relevance
“…Emergence of de novo donor specific antibodies has also been recently been reported in a pediatric heart transplant recipient who was infected with SARS-CoV-2. 44 Kidney allograft recipients may therefore be at increased risk for developing de novo DSAs and active antibody-mediated rejection after SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Emergence of de novo donor specific antibodies has also been recently been reported in a pediatric heart transplant recipient who was infected with SARS-CoV-2. 44 Kidney allograft recipients may therefore be at increased risk for developing de novo DSAs and active antibody-mediated rejection after SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the case report by Russell MR et al [ 10 ], the patient was admitted to receive intravenous immunoglobulin 1 week after surveillance laboratory studies showed anti-human leukocyte antigen antibody. Because of the history of cough, SARS-CoV-2 reverse transcriptase polymerase chain reaction test was performed and returned positive.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the history of cough, SARS-CoV-2 reverse transcriptase polymerase chain reaction test was performed and returned positive. They suggested that careful measurement of donor-specific antibodies be undertaken in heart transplant survivors of COVID-19 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Best practice development has focused on the epidemiology and impact of SARS-CoV-2 in SOT patients, community penetrance of COVID-19 disease and school-specific infection prevention intervention implementation in a consensus document recently published (54). Although pediatric SOT recipients are at increased risk for severe manifestations of common infections (55), case reports and case series of SARS-CoV-2 infection in pediatric SOT emerging thus far suggest pediatric SOT recipients are at similar risk and present with a similar spectrum of infection as other children (19,(56)(57)(58)(59); however data are significantly limited and caution is still recommended. For example, an evaluation of the UK Transplant Registry linked with the National Health Service Digital Tracing Services identified only three cases of SARS-CoV-2 among 1,703 pediatric SOT recipients (0.5%) and no deaths occurred during a 4-month period during the height of the first wave of the pandemic in the UK (60).…”
Section: Sars-cov-2 and School In Sot Recipientsmentioning
confidence: 99%